2015
DOI: 10.1584/jpestics.d15-020
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and biological evaluation of novel <i>N</i>-pyridylpyrazole derivatives containing 1,2,3-triazole moieties

Abstract: Based on the commercial insecticide chlorantraniliprole, a series of novel N-pyridylpyrazole derivatives containing 1,2,3-triazole moieties were designed and synthesized via Huisgen cycloaddition reaction. The insecticidal activities of the new compounds against the oriental armyworm (Mythimna separata) were evaluated, of which compound Ib with an Nisopropyl anthranilic amide moiety displayed 100% larvicidal activities against Mythimna separata at a concentration of 10 mg/L. Moreover, the fungicidal activities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…The herbicidal, fungicidal, insecticidal activities of the title compound were measured according to the reference method [4][5][6]. The results indicated that the title compound showed weak inhibitory activity against Fusarium oxysporum, Rhizoctonia solani, Gibberella zeae, Botryospuaeria berengeriana and Colletotrichum gossypii at 50 ppm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The herbicidal, fungicidal, insecticidal activities of the title compound were measured according to the reference method [4][5][6]. The results indicated that the title compound showed weak inhibitory activity against Fusarium oxysporum, Rhizoctonia solani, Gibberella zeae, Botryospuaeria berengeriana and Colletotrichum gossypii at 50 ppm, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Because agricultural pests can develop resistance rapidly all over the world, it is necessary to develop efficient insecticides with novel structures and modes of action . As a selective activator of the insect ryanodine receptor, chlorantraniliprole ( A , Scheme ) which has attracted considerable attention for decades because of its exceptional insecticidal activity on a broad spectrum and low mammalian toxicity . Recently, Li and Song et al .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Li and Song et al . have designed and synthesized series of novel N ‐pyridylpyrazole derivatives on the basis of the structure of chlorantraniliprole . Their results demonstrated that the modifications in the structure of chlorantraniliprole are still attractive.…”
Section: Introductionmentioning
confidence: 99%
“…‐ The 1,2,3 moiety does not occur in nature, although the synthetic molecules containing 1,2,3‐triazole unit show diverse biological activities including anti‐obesity, antiallergic, antibacterial, antiparasitic, herbicidal, fungicidal, and anti‐HIV 1,2,3‐triazole moieties are stable to metabolic degradation, oxidative/reductions conditions, and are capable of dipole‐dipole interactions and hydrogen bonding, which can be favourable in the binding of biomolecular targets and for solubility …”
Section: Introductionmentioning
confidence: 99%